Accurate LC‐ESI‐MS/MS quantification of 2′‐deoxymugineic acid in soil and root related samples employing porous graphitic carbon as stationary phase and a 13C4‐labeled internal standard. Issue 9 (10th March 2014) - Schindlegger, Yvonne; Oburger, Eva; Gruber, Barbara; Schenkeveld, Walter D. C.; Kraemer, Stephan M.; Puschenreiter, Markus; Koellensperger, Gunda; Hann, Stephan; Klampfl, Christian W.
<x xml:space="preserve">Abstract</x> For the first time the phytosiderophore 2′‐deoxymugineic acid (DMA) could be accurately quantified by LC‐MS/MS in plant and soil related samples. For this purpose a novel chromatographic method employing porous graphitic carbon as stationary phase combined with ESI‐MS/MS detection in selected reaction monitoring was developed. Isotope dilution was implemented by using in‐house synthesized DMA as external calibrant and 13C4‐labeled DMA as internal standard (concentration levels of standards 0.1–80 μM, determination coefficient of linear regression R2 > 0.9995). Sample preparation involved acidification of the samples in order to obtain complete dissociation of metal‐DMA complexes. Excellent matrix related LOD and LOQ depending on different experimental setups were obtained in the range of 3–34 nM and 11–113 nM, respectively. Standard addition experiments and the implementation of the internal 13C4‐DMA standard proved the accuracy of the quantification strategy even in complex matrices such as soil solution. The repeatability of the method, including sample preparation, expressed as short‐ and long term precision was below 4 and 5% RSD, respectively. Finally, application in the context of plant and soil research to samples from rhizosphere sampling via micro suction cups, from soil solutions and soil adsorption/extraction studies revealed a DMA concentration range from 0.1 to 235 μM.